Sekolah Kader Protector Jaten: Upaya peningkatan pengetahuan dan keterampilan kader remaja posbindu PTM di Dusun Jaten, Yogyakarta - Ifa Najiyati; Beauty Octavia Mahardany; Yana Yulyana; Supriyati Supriyati; Anggi Lukman Wicaksana (Journal of Community Empowerment for Health, 2019)
Data from the Community and Family Health Care (CFHC) Faculty of Medicine, Public Health,and Nursing Universitas Gadjah Mada (UGM) in 2018 indicated that 32.6% of families in Jaten had hypertension. The results of community analysis indicated that non-communicable diseases (NCDs) were a major problem in Jaten. One of the measures to control NCDs is through integrated development and coaching post (called by posbindu PTM). The target age of posbindu PTM started from adolescence which is 15 years old. Adolescents are vulnerable group. Biological and psychological changes in adolescence have consequences that can affect their health for a lifetime. Posbindu PTM in Jaten was established in March 2018. However, the participation of adolescents was low. Early Detection and Disease Prevention by Jaten’s Adolescent Program (Protector Jaten) is designed to provide access and health services for adolescents. This program began with recruiting adolescents to be cadres and continued with cadre school. Adolescent cadres were equipped with knowledge and skills to do their duties in posbindu PTM. This study aimed to assess and explore School for Adolescent Cadres Protector Jaten to increase knowledge and skills of adolescent cadres about implementation of posbindu PTM. The design of this study was a pre-experimentalwith one group pre-test post-test design and mixed methods using the Kirkpatrick model level 1 and 2. The quantitative method was carried out using a questionnaire to 11 adolescent cadres. The qualitative method used observation to measure skills and semi-structural interviews on 5 adolescent cadres about the effect of School for Adolescent Cadres Protector Jaten. Total of 63,6% adolescent cadres were females with range of ages between 22 and 24 years old. The mean score of adolescent cadres’ knowledge was 6,5 and 8,6 for pre and post School for Adolescent Cadres Protector Jaten. There was a significant effectof School for Adolescent Cadres Protector Jaten on adolescent cadres’s knowledge (p = 0,003). There was increasing skills of adolescent cadres about the implementation of posbindu PTM. The result of interview showed that School for Adolescent Cadres Protector Jaten improved the knowledge, skill, and awareness in preventing NCDs. School for Adolescent Cadres Protector Jaten increased knowledge and skills about the implementation of posbindu PTM. Adolescent cadres still require assistance in implementing posbindu PTM as well as a refreshing program to maintain the implementation of posbindu PTM.